Optimalisas Hasil Belajar Peserta Didik Pada Mata Pelajaran Matematika KD 3.6/4.6 Kesebangunan dan Kongruensi Melalui Model Project Based Learning Metode Pemberian Tugas Pada Kelas IX.2 MTsN 1 Payakumbuh Semester Genap TP 2021/2022 - Rosita Rosita (Journal on Education, 2022)
The purpose of this study was to determine the increase in student learning outcomes in Mathematics subjects entitled "Optimizing Student Learning Outcomes for Mathematics Subjects KD 3.6/4.6 Congruence and Congruence Through Project Based Learning Methods of Division of Tasks in class IX. 2 MTsN 1 Payakumbuh City Even Semester 2021/2022.” This research method uses Classroom Action Research. This study consisted of four stages, namely, planning, action, observation, and reflection which was carried out in two cycles at MTsN 1 Payakumbuh City. The research population is class IX.2 students, researchers and collaborators. This research took place from 3 February 2022 to 11 March 2022. The data was processed in each cycle and then analyzed using percentages. The results obtained from this paper are by using the p model Project based learning, the Task Division method can improve student learning outcomes. This is evident from the increase in the learning outcomes of pre-cycle students (knowledge and skills) with cycle 1 being 9.1% and the increase in learning outcomes in cycle 1 (knowledge and skills) with cycle 2 being 2.5%. The conclusion obtained from this paper is that the use of the Problem Based learning model of the Division of Tasks method can improve the learning outcomes of students in class IX. 2 MTsN 1 Payakumbuh City even semester 2021/2022.